Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses two key issues of the Belgian economy: (1) making public expenditure more efficient and (2) addressing the Belgian labor market-segmentations and distortions. Belgium faces fiscal challenges that call for a substantial consolidation over the medium term. The sizable expenditure reduction contemplated by the authorities will be difficult without deeper structural reforms. Reforms that improve the efficiency of public spending can help underpin fiscal adjustment while minimizing the drag on growth and protect social cohesion. The Belgian labor market suffers from rigidities and fragmentation. The design of policies to increase employment rates among these vulnerable labor market segments requires a thorough reflection of symptoms and underlying causes.